Skip to content
Related Articles

# Write the Additive Inverse of 3/13

• Last Updated : 21 Jul, 2021

Any number that can bring the entire result to zero is an additive inverse. In other words, when a number is multiplied by its additive inverse, the result is zero. If we take the number 1 and multiply it by -1, the outcome is zero. As a result, 1’s additive inverse is -1.

Even in actual life, everything we perceive can be reduced to zero if the exact inverse is discovered. The correct amount of fire and ice, for example, will cancel each other out and the outcome will be zero.

The value of an additive inverse of a number is defined as the value that when added to the original number yields zero. It’s the amount we add to a number to make it equal zero.

If x is an original number, then its additive inverse is minus x, or -x, as follows:

x + (-x) = x – x = 0

Hence, Additive inverse of x is -x.

Now, in case of -x i.e. the additive inverse of -x must be x or positive as follows:

(-x) + x = -x + x = 0

Examples of Additive Inverse

1. The additive inverse of 1 is -1. (Since, 1 + (-1) = 0)
2. The additive inverse of 10 is -10. (Since, 10 + (-10) = 0)
3. The additive inverse of 101 is -101, (Since, 101 + (-101) = 0)
4. The additive inverse of -10000 is 10000. (Since, (-10000) + 10000 = 0)

Similarly, in case of fractions the additive inverse are given as:

If (p/q) is an original fraction, then its additive inverse is minus (p/q), or (-p/q), as follows:

p/q + (-p/q) = p/q – p/q = 0

Hence, Additive inverse of p/q is -p/q.

Now, in the case of (-p/q) i.e. the additive inverse of (-p/q) must be (p/q) or positive as follows:

(-p/q) + p/q = -p/q + p/q = 0

### Write the Additive Inverse of 3/13

Solution:

The given fraction is 3/13.

As we know that, the additive inverse of any fraction is given as:

p/q + (-p/q) = p/q – p/q = 0

This implies, the additive inverse of p/q is -p/q.

Now, in case of (-p/q) i.e. the additive inverse of (-p/q) must be (p/q) or positive as follows:

(-p/q) + p/q = -p/q + p/q = 0

Similarly, the additive inverse of 3/13 is -3/13 as follows:

(3/13) + (-3/13) = 0

Hence, the additive inverse of 3/13 is -3/13 or negative 3/13.

### Similar Questions

Question 1: What is the additive inverse of -5?

Answer:

The additive inverse of -5 is 5 as follows:

(-5) + 5 = -5 + 5 = 0

Question 2: What is the additive inverse of 9/1000?

Answer:

The additive inverse of 9/1000 is -9/1000 as follows:

9/1000 + (-9/1000) = 9/1000 – 9/1000 = 0

Question 3: What is the additive inverse of 55?

Answer:

The additive inverse of 55 is -55 as follows:

55 + (-55) = 55 – 55 = 0

Attention reader! Don’t stop learning now. Join the First-Step-to-DSA Course for Class 9 to 12 students , specifically designed to introduce data structures and algorithms to the class 9 to 12 students

My Personal Notes arrow_drop_up